AN ANALYSIS OF EDUCATIONAL VALUE IN "FREEDOM WRITERS" MOVIE - Yumni Mulyadi, Tharifah Syarafina Titania Zata; Rosnija, Eni; Wardah, Wardah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This research aims to identify the educational value of the movie "freedom writers". This research used a descriptive qualitative approach. The object was movie "freedom writers". Data collection used was the documentation method. Technique of data analysis was documentary analysis. The conclusion of this research is that the substance of the educational value contained in the film "freedom writers" is the value of firmness, anti-racism and violence, justice, caring, never giving up, the teacher's role as a motivator, the teacher's role as a facilitator, cooperation, honesty, creativity, and freedom of expression. The movie freedom writers contains educational value that can increase student competence.